SPE Asia Pacific Oil and Gas Conference and Exhibition 2018
DOI: 10.2118/192076-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fines Migration During CO2 Injection Using Pore Scale Characterization

Abstract: Recent laboratory studies have shown fines migration induced decrease in rock permeability during CO2 injection. Fines migration is a pore scale phenomenon, yet previous laboratory studies did not conduct comprehensive pore scale characterization. This study utilizes integrated pore scale characterization techniques to study the phenomenon. We present CO2 injection experiments performed on two Berea sandstone samples. The core samples are characterized using nitrogen permeability, X-ray micro-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Injection of CO 2 -saturated brine results in a low pH that can cause dissolution of mineral cement and generation of particles with migration of fines (Othman et al, 2018b) Mathematically it has been shown (Huang et al, 2018) that wettability influences the interfacial forces acting on fine particles, with their subsequent associated displacement. Capillary forces or wettability can reduce injection when fine migration occurs (Guo et al, 2018;Chequer et al, 2018;Russell et al, 2018), with pore blockage during CO 2 sequestration tests (Othman et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injection of CO 2 -saturated brine results in a low pH that can cause dissolution of mineral cement and generation of particles with migration of fines (Othman et al, 2018b) Mathematically it has been shown (Huang et al, 2018) that wettability influences the interfacial forces acting on fine particles, with their subsequent associated displacement. Capillary forces or wettability can reduce injection when fine migration occurs (Guo et al, 2018;Chequer et al, 2018;Russell et al, 2018), with pore blockage during CO 2 sequestration tests (Othman et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…In the injection process into the reservoir, the mineral particles present can be detached, being suspended in the injected fluid and, when their size allows, strain in the pore throats during transport. This results in a significant decrease in the permeability of the porous medium due to the process known as fines migration, which can significantly influence the capacity of the injection wells by supplying fluid to the reservoir (Othman et al, 2018a;Othman et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%